(untitled) (Balneo and PRM Research Journal, 2024)
Background and Study Purpose.: The body composition study (Inbody 720/Biospace (Korea)) presents the advantage of a detailed exploration of some complex parameters, which can provide useful information related to the nutritional status and health of those evaluated. The purpose of the research is the comparative analysis of these indicators for pubertal girls, divided into two categories: handball practitioners and non-athletes. Material and Methods. The study participants come from 2 groups: 59 handball players/HB (Age=11.72±.82, Height =157.64±8.62, Weight =53.16±10.36) and 115 non-athletes/NA (Age=11.67±.75, Height = 155.33±7.16, Weight =48.84±10.40). The groups were investigated between March and April 2023. Results. The BMI values obtained were interpreted by calculating the international percentiles, for the age range 2-19 years. The group of handball players presents superior values regarding weight, height, BMI percentiles, bone mineral content, body cell mass, basal metabolic rate, arm muscle circumference and Fitness score. According to the BMI classification, there are no handball players in the underweight class, and 40% of the HB group and 31% of the NA belong to the Overweight and Obese classes. Better values for lean mass of the HB group are reported, for all body areas and body segments, with significant differences compared to the NA group. Fat control recommendations indicate the need to remove more fat for the NA group and add more muscle (over 80% of the components of this group). Both groups have problems with abdominal obesity, approximately a quarter of the students having WHR values within Abd. Obesity. The Strength levels indicator shows better values for the HB group (majority in the Normal and Developed categories), and over a quarter of the NA group has problems at the lower body level (fall within the Weak level). Conclusions. According to the values provided by Obesity Degree by Body Fat, one third of the female students of both groups have obesity problems, which is an alarm signal regarding the health of the young generation, aspects also confirmed by the analyzed studies. The muscle/fat ratio indicates for the NA group lower percentage values for muscle/SMM and higher for fat/BFM, compared to the HB group, so the physical activity specific to handball players has a determining role in explaining these values. Keywords: body composition, handball, differences, fitness score, Body mass index, obesity